Shake Hands with a Robot – Understanding Frontstage Employees' Adoption of Service Robots in Retailing - Patrick Meyer; Philipp Spreer; Klaus Gutknecht (Marketing Review St.Gallen, 2022)
The use of service robots in retailing has been steadily gaining momentum over the past decade. Research has primarily focused on customer adoption. However, without addressing the reservations of frontstage employees, an effective adoption of service robots will not happen. This study presents a measurement instrument for the drivers of and barriers to adoption by frontstage employees and derives success factors.
Keywords: 650